2016
DOI: 10.1007/s12630-016-0797-5
|View full text |Cite
|
Sign up to set email alerts
|

L-carnitine reduces susceptibility to bupivacaine-induced cardiotoxicity: an experimental study in rats

Abstract: These findings suggest that acute administration of L-carnitine 100 mg·kg decreases susceptibility to bupivacaine cardiotoxicity, but is ineffective during resuscitation from bupivacaine-induced cardiac arrest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Similar findings were obtained in murine models of moderate carnitine deficiency induced with carnitine depleting agents such as pivalic acid, mildronate and d-carnitine [77][78][79]. We have shown that rats exposed to a moderate reduction in cardiac l-carnitine content are more susceptible to myocardial injury induced by β-adrenergic stimulation (isoproterenol) along with an unanticipated high mortality rate [77].…”
Section: Metabolic Features Of L-carnitine Relevant To Pd Therapysupporting
confidence: 79%
See 1 more Smart Citation
“…Similar findings were obtained in murine models of moderate carnitine deficiency induced with carnitine depleting agents such as pivalic acid, mildronate and d-carnitine [77][78][79]. We have shown that rats exposed to a moderate reduction in cardiac l-carnitine content are more susceptible to myocardial injury induced by β-adrenergic stimulation (isoproterenol) along with an unanticipated high mortality rate [77].…”
Section: Metabolic Features Of L-carnitine Relevant To Pd Therapysupporting
confidence: 79%
“…Indeed, l-carnitine supplementation of such l-carnitine deficient mice subjected to ascending aortic constriction not only prevented cardiac injury, but it also increased survival rate compared to untreated mice. A moderate heart carnitine deficiency induced by d-carnitine treatment increased sensitivity to bupivacaine-induced asystole, whereas l-carnitine repletion completely reversed such effect [78]. This experimental study was conducted by the same authors after they experienced a case of peri-operative cardiac arrest in a carnitine deficient child (valproate-induced) in the context of intravascular administration of bupivacaine, an anaesthetic known to exert cardiotoxic side effects [78].…”
Section: Metabolic Features Of L-carnitine Relevant To Pd Therapymentioning
confidence: 99%
“…In 1997, Weinberg et al reported that subcutaneous injection of a small dose of bupivacaine (non-toxic dose: 22 mg) in a 16-year-old female patient with isovaleric acidemia yielded unexpected ventricular arrhythmia likely caused by secondary systemic carnitine deficiency 7 . Based on these reports, this unexpected ventricular arrhythmia was likely associated with increased susceptibility to bupivacaine toxicity due to carnitine deficiency 7 - 11 . In addition, Wong et al reported ventricular arrhythmia caused by the presumed intravascular migration of an epidural catheter in a 6-year-old male patient with both secondary carnitine deficiency due to long-term treatment with valproic acid and a non-toxic dose of bupivacaine (0.58 mg/ml) 12 .…”
Section: Introductionmentioning
confidence: 88%
“…Bupivacaine prevents long-chain fatty acid transport to the mitochondria by inhibiting carnitine-acylcarnitine translocase 8 - 10 . Pretreatment with L-carnitine before bupivacaine-induced asystole in rats decreased the susceptibility to bupivacaine-induced cardiac toxicity 11 . In 1997, Weinberg et al reported that subcutaneous injection of a small dose of bupivacaine (non-toxic dose: 22 mg) in a 16-year-old female patient with isovaleric acidemia yielded unexpected ventricular arrhythmia likely caused by secondary systemic carnitine deficiency 7 .…”
Section: Introductionmentioning
confidence: 94%
“…GIII: in which rats were subcutaneously injected with isoproterenol with same dose and duration plus vitamin E (100 IU/kg BW) intraperitoneal injection daily for 4 weeks according to Gayathri et al, [8]. GIV: in which rats were subcutaneously injected with isoproterenol plus intraperitoneal daily injection of L-carnitine (100 mg/kg BW) for 4 weeks according to Wong et al [33].…”
Section: Experimental Protocolsmentioning
confidence: 99%